Gains from International Diversification: 1968-85 Returns on Portfolios of Stocks and Bonds: Discussion - Crouhy, Michel (Journal of Finance, 1987)
Michel Crouhy, Gains from International Diversification: 1968-85 Returns on Portfolios of Stocks and Bonds: Discussion, The Journal of Finance, Vol. 42, No. 3, Papers and Proceedings of the Forty-Fifth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 28-30, 1986 (Jul., 1987), pp. 739-741